Life cycle analysis of small scale pellet boilers characterized by high efficiency and low emissions. (1st October 2015) - Monteleone, B.; Chiesa, M.; Marzuoli, R.; Verma, V.K.; Schwarz, M.; Carlon, E.; Schmidl, C.; Ballarin Denti, A.
Highlights: LCA was performed on innovative small scale pellet boilers. Pellet boilers impacts were compared to oil and natural gas boilers impacts. Both literature and experimental data were used for life cycle analysis. The environmental impact due to all life cycle phases was envisaged. Sensitivity tests evidenced realistic ways for pellet boilers impact reduction. Abstract: This study focuses on the environmental impact assessment through Life Cycle Analysis (LCA) of two innovative 10 kW pellet boilers. In particular, the second boiler represents a technological evolution of the first one developed to improve its performance in terms of efficiency and environmental impact. For both boilers, emission factors measured during laboratory tests (full load tests and specific load cycle tests representative of real life boiler operation) have been used as input data in the life cycle analysis. The SimaPro software (v.8.0.4.30) was used for the LCA and the ReCiPe Midpoint method (European version H) was chosen to assess the environmental impact of all boilers (according to LCA ISO standards). In addition, the ReCiPe Endpoint method was used to compare the final results of all 5 boilers with literature data. The pelletisation process represented the most relevant share of the overall environmental impact followed by the operational phase, the manufacturing phase and the disposal phase. A sensitivity analysis performed on the most efficient pellet boiler evidenced the variation of the boiler's environmental impact as a function of PM10 and NOX emission factors with respect to emission factors monitored during boiler full load operation. Moreover, the reduction of the boiler's weight and the adoption of new electronic components led to a consistent reduction (−18%) of its environmental impact with respect to the previous technology. A second LCA has been carried on for a 15 kW oil boiler, a 15 kW natural gas boiler and a 15 kW pellet boiler, representative of the state of the art of EU technology, to finally compare all LCA results. Results showed the environmental impact reduction of BW10 and BW10 2 pellet boilers with respect to fossil fuelled boilers mainly due to their reduced impact on CC (reductions by 86–90% and 88–91% with respect to the NG and oil boilers respectively), NLT (reductions by 77–79% and 86–87% with respect to the NG and oil boilers respectively) and FD (reductions by 89–92% and 90–93% with respect to the NG and oil boilers respectively) ReCiPe Midpoint subcategories.